Efeitos do treino em esteira com suporte parcial de peso e do método de facilitação neuromuscular proprioceptiva na marcha hemiparética: estudo comparativo - Ribeiro, Tatiana Souza (2011)
Objective: To compare the effects of the treadmill training with partial body-weight support (TPBWS) and Proprioceptive Neuromuscular Facilitation (PNF) method on gait of subjects with chronic stroke. Design: Quasi-experimental study. Setting: Laboratorial research. Participants: Twenty-three subjects (13 men and 10 women), with a mean age of 56,7 ± 8,0 years and a mean time since the onset of the stroke of 27,7 ± 20,3 months, and able to walk with personal assistance or assistive devices. Interventions: Two experimental groups underwent gait training based on PNF method (PNF group, n=11) or using the TPBWS - Gait Trainer System 2, Biodex, USA (TPBWS group, n=12), for three weekly sessions, during four weeks. Measures: Evaluation of motor function - using the Stroke Rehabilitation Assessment of Movement (STREAM) and the motor subscale of the Functional Independence Measure (motor FIM) -, and kinematic gait analyze with the Qualisys System (Qualisys Medical AB, Gothenburg, Sweden) were carried out before and after the interventions. Results: Increases in the STREAM scores (F=49.189, P<0.001) and in motor FIM scores (F=7.093, P=0.016), as well as improvement in symmetry ratio (F=7.729, P=0.012) were observed for both groups. Speed, stride length and double-support time showed no change after training. Differences between groups were observed only for the maximum ankle dorsiflexion over the swing phase (F=6.046, P=0.024), which showed an increase for the PNF group. Other angular parameters remain unchanged. Conclusion: Improvement in motor function and in gait symmetry was observed for both groups, suggesting similarity of interventions. The cost-effectiveness of each treatment should be considered for your choice